Using Global Positioning System Technology to Manage Human-Black Bear Incidents at Yosemite National Park - Rachel L. Mazur; Ryan M. Leahy; Caitlin J. Lee-Roney; Kathleen E. Patrick (Human-Wildlife Interactions, 2018)
Managing human–bear (Ursus spp.) incidents is a top management priority in national parks inhabited by bears. Yosemite National Park (Yosemite), located in the Sierra Nevada in California, USA, receives up to 5 million visitors annually. It is also home to 300–500 black bears (U. americanus). Yosemite has an extensive history of black bear research, educational programs, and innovative solutions for reducing human–bear incidents. Despite this, human–bear incidents peaked in 1998 at 1,584. The resulting political fallout led to Yosemite receiving funds to expand its bear management program, including increasing its staffing and garbage pick-up, and improving the park’s bear-resistant infrastructure. In 2011, Yosemite reached a milestone when it recorded only 114 human–bear incidents—a 93% decrease from the 1998 high. To sustain this lower level of incidents while facing shrinking budgets and increasing visitation, bear managers turned to more modern technology. From 2014–2018, we evaluated the effectiveness of using global positioning system (GPS) collars to manage bears more proactively, increase staff and public engagement with bears, and gain insight into the bears’ spatial and temporal movements. The GPS collars were effective in achieving these goals, while also improving both our time management and our communication with park management. By the end of November 2018, Yosemite had recorded only 22 human–bear incidents—a 99% decrease from the 1998 high. The GPS collars are now an integral part of the Yosemite bear management program. We provide recommendations on how GPS technology may help other parks reduce human–bear incidents.